Emergency hospital services utilization in Lleida (Spain): A cross-sectional study of immigrant and Spanish-born populations - Soler-González Jorge; Cabré Xavier; Rué Montserrat; Bosch Anna; Almirall Mercè; Serna Maria (BMC, 2008)
Abstract Background The use of emergency hospital services (EHS) has increased steadily in Spain in the last decade while the number of immigrants has increased dramatically. Studies show that immigrants use EHS differently than native-born individuals, and this work investigates demographics, diagnoses and utilization rates of EHS in Lleida (Spain). Methods Cross-sectional study of all the 96,916 EHS visits by patients 15 to 64 years old, attended during the years 2004 and 2005 in a public teaching hospital. Demographic data, diagnoses of the EHS visits, frequency of hospital admissions, mortality and diagnoses at hospital discharge were obtained. Utilization rates were estimated by group of origin. Poisson regression was used to estimate the rate ratios of being visited in the EHS with respect to the Spanish-born population. Results Immigrants from low-income countries use EHS services more than the Spanish-born population. Differences in utilization patterns are particularly marked for Maghrebi men and women and sub-Saharan women. Immigrant males are at lower risk of being admitted to the hospital, as compared with Spanish-born males. On the other hand, immigrant women are at higher risk of being admitted. After excluding the visits with gynecologic and obstetric diagnoses, women from sub-Saharan Africa and the Maghreb are still at a higher risk of being admitted than their Spanish-born counterparts. Conclusion In Lleida (Spain), immigrants use more EHS than the Spanish born population. Future research should indicate whether the same pattern is found in other areas of Spain and whether EHS use is attributable to health needs, barriers to access to the primary care services or similarities in the way immigrants access health care in their countries of origin.